Operating performance following corporate acquisitions: Does the organisational form of the target matter?. Issue 1 (April 2016) - Shams, Syed M.M.; Gunasekarage, Abeyratna
Abstract: We compare the long-run operating performance of private target acquirers and public target acquirers using a sample of Australian acquisitions. While private target acquirers realise significantly higher abnormal returns during the announcement period of acquisitions than public target acquirers, there is no significant difference in their operating performance during the post-acquisition period. Relative size has differential effects on the performance of two types of acquirers. Significant performance improvements are possible when private target acquirers make relatively large acquisitions and when public target acquirers acquire relatively small acquisitions. Acquisitions of private targets are also associated with significant performance improvements if they are undertaken by experienced acquirers.